Determination of Seminal Concentration of Fingolimod and Fingolimod‐Phosphate in Multiple Sclerosis Patients Receiving Chronic Treatment With Fingolimod. Issue 2 (19th December 2017) - David, Olivier J.; Berwick, Amy; Pezous, Nicole; Lang, Michael; Tiel‐Wilck, Klaus; Ziemssen, Tjalf; Li, Peng; Hara, Hisanori; Schmouder, Robert
Abstract: The safety profile of fingolimod 0.5 mg, approved therapy for relapsing multiple sclerosis, is well established in clinical and real‐world studies. As fingolimod is teratogenic in rats, it was considered important to assess the concentrations of fingolimod and its active metabolite, fingolimod‐phosphate, in the semen of male patients on treatment and the risk of harming a fetus in a pregnant partner. In this multicenter open‐label study, 13 male patients receiving fingolimod for at least 6 months provided 1 semen and 1 blood sample for analyte concentration measurements. The steady‐state seminal concentrations of fingolimod and fingolimod‐phosphate were close to those simultaneously observed in blood. The amount of fingolimod‐related material in 10 mL of ejaculate was estimated to be 47.5 ng. The estimated fingolimod and fingolimod‐phosphate blood Cmax values in a woman having regular sexual intercourse with a male patient treated with fingolimod 0.5 mg were approximately 400 and 2400 times smaller than the estimated values in the embryo‐fetal development study in rats at the no‐observed‐adverse‐event level. Consequently, the risk of harming a fetus in a pregnant woman is considered extremely unlikely.